ความต้านทานการแตกหักในฟันคลองรากไม่กลมที่บูรณะด้วยระบบเดือยฟันคอมโพสิตเสริมเส้นใยที่แตกต่างกัน - วีรนุช ทองงาม (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Purpose: To compare the fracture resistance and fracture mode of non-circular root canal premolars restored with different fiber-reinforced composite post systems. Materials and methods: Fifty non-circular single root canal premolars were randomly assigned to five groups (n=10). Coronal portions of the teeth were removed at a level 2 mm above the CEJ. The samples in group 1-3 were prepared by using FibreKleer® drill; group 1 was restored with FibreKleer® posts; group 2, FibreKleer® posts and Reforpin®; group 3, FibreKleer® posts were relined with Multicore® flow (anatomical post). The samples in group 4 and 5 were prepared by using Evolution® drill; group 4 used the same method with group 3, group 5 was restored with Evolution® post and core. All posts and cores and metallic crowns were cemented with Variolink® II. The samples were loaded in universal testing machine (Instron®). Mean fracture loads of group 1-3 were analyzed using the one-way ANOVA, Tukey multiple comparison test (p<0.05). Those of group 4 and 5 were analyzed using the Student’s T-test. The fracture modes of all experimental groups were analyzed. Results: Mean fracture resistance of group 1 was statistically significant lower than group 2 and 3 (p<0.05) and these two groups were not significantly different. No statistically significant difference was found between group 4 and 5 (p>0.05). Restorable failures were found in group 1-5 were 60, 70, 70, 60 and 60 percents, respectively. Conclusion: Fracture resistances of non-circular root canal teeth restored with fiber-reinforced composite posts cemented with resin cement were lower than other systems. Teeth restored with all systems most showed restorable failures.